Lung Abscess: Literature Review of Risk Factors, Classification, Clinical Manifestations, Diagnosis, and Prevention - Nitzana, Lale Nubya; Hasanah, Mielosita; Mikailla, Romy Healthy; Anugrah, Yunan Prabu Jaya; Ilmiah, Janiya Abdila; Ajmala, Indana Eva (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
A lung abscess is the formation of a thick-walled cavity filled with purulent material due to suppuration and necrosis of the lung parenchyma. Cases of lung abscess are relatively rare today and were most common in the pre-prebiotic era due to the lack of treatment for bacterial infections. This literature review aims to obtain information related to lung abscess its etiology, diagnostics, and treatment options. The article was compiled using a literature search through databases such as PubMed, ScienceDirect, and Google Scholar using the keyword